2021
DOI: 10.1037/tra0001005
|View full text |Cite
|
Sign up to set email alerts
|

Personal growth in the transition to parenthood following recent parental loss.

Abstract: Objective: Although the factors associated with personal growth (PG) in the transition to parenthood have been studied in recent years, the impact of a previous stressful event has been rarely considered. This study explores the possibility that parents who lost their own parent in the years leading up to the birth of their first child will report enhanced PG. It examines the unique and combined contribution to PG in the transition to parenthood of recent parental loss, as well as the bond with the parents, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 67 publications
4
14
0
Order By: Relevance
“…Parents who reported higher parental care reported a decrease in PD over time, which in turn was associated with an increase in PG over time, while those who reported higher maternal overprotection reported an increase in PD, which was associated with a decrease in PG. These findings confirm the importance of the parenting style to which the individual is exposed during childhood and adolescence for their experience of distress or growth as adults (Ben-Yaakov & Taubman – Ben-Ari, 2021; Grant et al, 2012; Matthey et al, 2000; Parade et al, 2014; Willinger et al, 2005). They indicate that the PG of new parents is not only affected by their current mental state, but that the seeds were planted much earlier by the type of bond they had with their own parents.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Parents who reported higher parental care reported a decrease in PD over time, which in turn was associated with an increase in PG over time, while those who reported higher maternal overprotection reported an increase in PD, which was associated with a decrease in PG. These findings confirm the importance of the parenting style to which the individual is exposed during childhood and adolescence for their experience of distress or growth as adults (Ben-Yaakov & Taubman – Ben-Ari, 2021; Grant et al, 2012; Matthey et al, 2000; Parade et al, 2014; Willinger et al, 2005). They indicate that the PG of new parents is not only affected by their current mental state, but that the seeds were planted much earlier by the type of bond they had with their own parents.…”
Section: Discussionsupporting
confidence: 73%
“…The present study provides evidence that parental care may not only contribute to the experience of PG itself, but to its increase over time as well. The finding that parents who report on higher maternal (although not paternal) overprotection experience an increase in PG is notable, as a previous study found that lower parental overprotection was associated with higher PG during the first year following the transition to parenthood (Ben-Yaakov & Taubman – Ben-Ari, 2021). Taken together, these findings suggest that during the child’s first year, which tends to be especially challenging for new parents, those who experienced parental overprotection during their own early years have a lower potential to experience PG.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Further, the pandemic has increased the amount of unpaid care work (e.g., childcare, elder care), which is often covered by women, many of whom are mothers (Power, 2020). However, other researchers have found that fathers but not mothers experienced a higher level of parenting stress during the pandemic compared to a year prior (Taubman-Ben-Ari et al, 2021) and that fathers of older infants may be particularly at risk for COVID-19 related anxieties (Ben-Yaakov and Taubman-Ben-Ari, 2021). Based on this mixed evidence, no hypothesis was made.…”
Section: Moderators Of Family Resiliencementioning
confidence: 99%